Prevalence of Helicobacter pylori infection and related gastroduodenal lesions in spouses of Helicobacter pylori positive patients with duodenal ulcer. Issue 5 (November 1996) - Parente, F; Maconi, G; Sangaletti, O; Minguzzi, M; Vago, L; Rossi, E; Bianchi Porro, G
Abstract : BACKGROUND: To date, very few studies have evaluated the risk of infection among spouses of Helicobacter pylori positive patients and their results are conflicting. AIM: To assess the seroprevalence of H pylori infection in spouse of H pylori positive patients with duodenal ulcer as compared with age and sex matched volunteer blood donors, as well as the frequency of endoscopic gastroduodenal lesions in these spouses, according to the presence or absence of gastrointestinal complaints. METHODS: Some 124 spouses (48% males) of patients with duodenal ulcer consecutively seen over a 10 month period were studied. They were all screened for serum IgG anti-H pylori antibodies and asked to complete a questionnaire with particular reference to the presence of chronic or recurrent dyspepsia. Upper gastrointestinal tract endoscopy with antral and corpus biopsy specimens taken for histological examination and urease rapid test was offered to all seropositive spouses. Volunteer blood donors (248), living in Milan and matched for age, sex, north-south origins, and socioeconomic status to the cases, were used as controls. RESULTS: Spouses of patients with duodenal ulcer had a significantly higher seroprevalence of H pylori infection than controls (71% v 58%, p < 0.05); 30 of 88 (34%) H pylori positive spouses complained of dyspeptic symptoms compared with only four of 34 (12%) seronegative spouses (p < 0.02). At endoscopy, H pylori infection was confirmed in 48 of 49 (98%) seropositive spouses. The endoscopic findings in those spouses showed active duodenal ulcer in eight (17%), duodenal scar and cap deformity in two (4%), active gastric ulcer in two (4%), erosive duodenitis in three (6%), antral erosions in two (4%), antral erosions plus duodenitis in one, and peptic oesophagitis in another patient. The prevalence of major endoscopic lesions was significantly higher in symptomatic spouses than in those who had never been symptomatic. CONCLUSIONS: These findings show that being the spouse of an H pylori positive patient with duodenal ulcer may increase the risk of H pylori colonisation and perhaps of peptic ulcer disease, and raises questions as to whether serological screening of cohabiting partners of H pylori positive patients with duodenal ulcer may be indicated.